Geographic proximity and firm-university innovation linkages: Evidence from Great Britain - Laura Abramovsky; Helen Simpson (Institute for Fiscal Studies (IFS), 2009)
We investigate evidence for spatially mediated knowledge transfer from university research. We examine whether firms locate their R&D labs near universities, and whether those that do are more likely to co-operate with, or source knowledge from universities. We find that pharmaceutical firms locate R&D near to frontier chemistry research departments, consistent with accessing localised knowledge spillovers, but also linked to the presence of science parks. In industries such as chemicals and vehicles there is less evidence of immediate co-location, but those innovative firms that do locate near to relevant research departments are more likely to engage with universities.
Keywords: O3; R11; R13; I23; 330; Innovation; Geography; Spillovers; Public Research; Hochschulforschung; Innovation; Betriebliche Forschung; Spillover-Effekt; Betrieblicher Standort; Entfernung; Großbritannien